Optimisation of kitchen waste composting - Abdullah, Norazlin (2011)
The problems of limited spaces for new opening of landfills and shortened life span of existing landfills have encouraged moves to reduce the amount of waste sent to landfills nationwide. Composting is a good recycling method to fully utilise all the organic materials from kitchen waste as it contains high nutritious matter within the waste. Optimisation of kitchen waste mixture proportions containing vegetable scraps, fish processing waste and newspaper or onion peels were investigated to find the optimum initial moisture content and carbon-to-nitrogen (CN) ratio to commence a more effective composting process. By applying the simplex-centroid mixture design method using a commercial software, the best mixtures proportion for blend with newspaper was at 48.5% of vegetable scraps, 17.7% of fish processing waste and 33.7% of newspaper, while for blend with onion peels, was at 44.0% of vegetable scraps, 19.7% of fish processing waste and 36.2% of onion peels to produce desired initial moisture content of 60% and CN ratio of 30. Utilising the optimal mixture proportions, following composting studies were conducted. The evaluation of the performance of the composting process was through measurements of CN ratio while monitoring its changes in temperature, moisture content, volatile solids content, pH, electrical conductivity, bulk density, colour, microbial numbers, headspace oxygen and carbon dioxide content. A kitchen waste composter which enables controlled composting conditions was designed and fabricated. It allows control of temperature inside the composter by either switching on or off a bulb attached on top of composter, and for control of moisture content of composting materials, the small holes at the bottom of the composter allows excessive water to flow out and then collect from the underside of the composter. The composter is insulated with 2 mm thickness of cloth to reduce the heat loss. The effects of using two bulking agents, newspaper and onion peels in kitchen waste composting were investigated by creating parallel composting using two kitchen waste composter. The optimum kitchen waste mixture compositing was used for a composting process of 30-days where temperature profiles were recorded and the CN ratio measured as indication of compost maturity. It was found that blends with onion peels decomposed more quickly than the newspaper, which by 30-days of composting period, the blends with onion peels produced end product with CN ratio of 8.15, while the newspaper with CN ratio of 37.04 and did not achieve any thermophilic stage. The results suggest that the onion peels are more suitable and the newspaper did not assist in acceleration of the composting process. The effects of kitchen waste compost load size were then investigated using kitchen waste mixtures with onion peels at 2 and 6 kg. The smaller load, 2 kg, decomposed more rapidly than the 6 kg because the temperature decreased to mesophilic temperature was 10 days earlier than in 6 kg and the CN ratio of 2 kg reaching 15 at 8 days earlier than 6 kg. Although the 2 kg of waste undergone shorter time of thermophilic phase at time range of about 3 days, it was still sufficient to kill the pathogens. This experiment suggests that a 2 kg of kitchen waste is enough to commence such composting. In accelerating composting processes, the use of microorganisms as an accelerant for this kitchen waste composting tested at 6 kg of kitchen waste with onion peels blend. Microbes’ cocktail consisting a mixture of seven types of bacteria and eight types of fungi priory isolated from soil, was added at the early stage of composting period in one composter while a control, a similar compost without adding the starter culture was compared. Analysis of variance (ANOVA) performed on the compost maturity indices did not show significant differences between the microbe added compost and control since p = 0.8158. The starter culture is therefore not necessarily to be added in the composting of food waste. In conclusion, composting of kitchen waste can be made simple and efficient with the right mixture proportion and type of waste to begin, using a minimal load of about 2 kg and without additional accelerant microbes. The effort of recycling kitchen waste is important in helping to build a sustainable environment that promises balanced ecosystems.